Eutectic mixture-directed kinetics of Diels-Alder reaction - Nagare, Amit S.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2011)
In the search for environmentally benign solvent media, a new class of solvents composed of mixtures of carbohydrates with urea or methylated urea has been noted to be effective in enhancing the reaction rates of a bimolecular organic reaction like the Diels-Alder reaction of cyclopentadiene with methyl acrylate. The viscosity of these media appears to be an important parameter in controlling the second order kinetics.
Keywords: carbohydrates; Cycloaddition; Diels-Alder reaction; Dimethylurea; kinetics; Reaction rates; solvent effects; Urea; viscosity